ІНСТРУМЕНТИ ПРАКТИЧНОЇ РЕАЛІЗАЦІЇ АНТИКРИЗОВОГО УПРАВЛІННЯ НА ПІДПРИЄМСТВАХ ТОРГІВЛІ - Лачкова Людмила; Борисова Аліна; Лачкова Вікторія (International Journal of Innovative Technologies in Economy, 2018)
The article deals with methodical approaches to the formation of the anti- crisis program of trade enterprises and drawing up of a plan for its implementation. During the research, it was determined that the basis of the crisis management program is diagnostics of the enterprise's development crisis, which should include not only probability of the enterprise bankruptcy, but also determine the existence of internal reserves of confrontation against it. In order to generalize and systematically present the developed anti-crisis measures and expected results after their implementation, it is proposed to use the methodology of problem structuring of the anti-crisis program and the schedule of their achievement, which contributed to the implementation of effective crisis management in trade enterprises.